A Conceptual Metaphor Analysis of English Songs from Jeff Satur’s Full Album ’Space Shuttle No.8’ - Maghfira, Hafsha Fadhla; Wibowo, Hanafi (Jurnal Penelitian Inovatif, 2025)
Metaphor is a figurative language that has an implicit meaning by comparing one thing to another which aims to refine the language and add aesthetics to a word. metaphors can be found in poetry, novels, and song lyrics. a sentence containing a metaphor does not directly convey the message contained in the writ-ing, for that the listener or reader must ascertain what message is actually conveyed in the sentence. In this research discusses the analysis of the conceptual type of metaphor based on the theory of lakoff and johnson and the meaning contained in the lyrics of English songs from jeff satur on the full album ’space shuttle no.8’. This research method uses a qualitative method with a qualitative descriptive approach that focuses on metaphor identification and interpretation. the data that has been obtained, is analyzed using conceptual metaphor analysis. The results show that there are 3 types of metaphors used based on Lakoff & Johnson theory in the English song lyrics, namely ontological metaphors, oriental metaphors, and structural metaphors. The researcher found that ontological metaphors were found the most with a per-centage of 50%, while oriental and structural metaphors had the same percentage with a percentage of 25%. The findings highlight how the role of metaphors in a sentence, especially in a song lyric, so that listeners get a deep impression and aesthetic value from a song lyric. This research contributes to linguis-tic research by showing the role of metaphor in a sentence, especially in a song lyric.